Assessing the Quality of Incident Investigations and its Effecton Safety Performance: a Study of the Ghanaian Mining Industry Mining, Metallurgy and Exploration - Eric Stemn; Maureen E. Hassall; Carmel Bofinger; David Cliff (Society for Mining, Metallurgy & Exploration)
Incident investigation is of utmost importance in most high-risk industries and is often used to improve organisational safety. This study was undertaken to examine the content of past incident investigation reports to determine the effectiveness of the incident investigations. The study uses a semi-quantitative method to assess the effectiveness of incident investigations in the Ghanaian mining industry by evaluating the quality of past investigation reports. The assessment tool consists of five elements with several indicators and rating scales for assessing the quality of an investigation report as a measure of the effectiveness of the investigation. The method was applied to 304 investigation reports of three Ghanaian large-scale gold mines, and the results correlated with incidence rates of the mines to determine if any relationship existed. The results showed that the mines differ significantly in the quality of their investigation reports, suggesting differences in the effectiveness of their investigations. In addition, the incidence rates of the mines negatively correlated with some elements of the assessment tool. In general, the method was found useful and revealed areas where improvement is needed.